Immunohistochemical Characteristics of Ischemic Process in Hippocampal Formation in Posterity of Female Rats after Labor Induction - Mamay, I. Yu.; Hryhorieva, O. A.; Dariy, V. I.; Мамай, Ірина Юріївна; Григор'єва, Олена Анатоліївна; Дарій, Володимир Іванович; Мамай, И. Ю.; Григорьева, О. А.; Дарий, В. И. (My University, 2021)
The response to perinatal hypoxia, developing in stimulating generic activity, is the activation of microglia, which induces the development of local inflammation of the brain and leads to the death of neurons. The formation of the hippocampus supports important physiological and behavioral functions, including spatial learning and memory, and is part of the brain, which is especially vulnerable to changes in blood glucose and oxygen. Thus, the study of the features of the development of hippocampal formation in the postnatal period after stimulating generic activity is relevant. The purpose of the study was to study the features of Glial fibrillary acidic protein and NeuN expression in the hippocampal formation in posterity of female rats after PgE2 injection for labor induction. Materials and methods. Pregnant females of the experimental group on the twenty-second day of pregnancy were injected intravaginally with PGE2 in the form of a gel to stimulate the generic activity. Birth occurred on the twenty-third day after conception. Birth in the intact group of rats occurred on the 23-24th day after conception. The large hemispheres of the rat brain were fixed in a 10% neutral formal solution, dehydrated in an ascending alcohol battery. For immunohistochemical studies, paraffin sections were used with 3 microns with a thickness of 3 microns. Glial fibrillary acidic protein Mouse Monoclonal Antibody (Santa Cruz Biotechnology, Inc.) is used to detect astrocytes (Santa Cruz Biotechnology, Inc.). NeuN Mouse Monoclonal Antibody (Santa Cruz Biotechnology, Inc.) was used to identify neurons on the 1st, 7th, 14th, 45th days after birth in histological cuts of hippocampus and gear, using a program for analyzing and processing images Image J, studied the relative area occupied by Glial fibrillary acidic protein + NeuN + cells. Data is processed by variation statistics. The results are reliable at p <0.05. All animal experiments were performed according to international principles of the European Convention for the Protection of Vertebrate Animals Used for Experimental and Other Scientific Purposes” (Strasbourg, 18.03.86) and the Law of Ukraine No. 1759-VI (15.12.2009) On the Protection of Animals from Cruelty. Results and discussion. We identified that by the changes in the hippocampus and the toothed gyrus of the rats after induction of labor, increased Glial fibrillary acidic protein expression on the first day after birth and reducing the NeuN expression on the 14th and 45th day of life in experimental animals compared to the control group were included. Conclusion. The density of the distribution of Glial fibrillary acidic protein + cells in the hippocampus and the dentate gyrus of rats changes wavily throughout the first month and a half of postnatal life. In the offspring of rats, after stimulation of labor on the first day of life, a reliable increase in the relative area occupied by Glial fibrillary acidic protein + astrocytes is determined compared to the control (49.3±2.6% and 36.8±5.9%, respectively). In the hippocampus and the dentate gyrus of rats after stimulation of labor during the first 45 days after birth, the gradual decrease in the relative area occupied by NeuN + neurons is determined, in contrast to the control animals, in which this index practically does not change. On the 14th and 45th days, the index of the relative area occupied by NeuN + neurons in experimental rats is reliably lower than in control (p <0.05).

Вивчення особливостей розвитку гиппокампальної формації в постнатальному періоді після стимуляції родової діяльності є актуальним. Мета. Вивчити особливості експресії GFAP і NeuN в гиппокампальної формації потомства щурів після інтравагінального введення PgE2 самкам для стимуляції родової діяльності. Матеріали та методи. Вагітним самкам експериментальної групи на 22й день вагітності для стимуляції родової діяльності вагінально вводили PgE2 у вигляді гелю. Великі півкулі головного мозку щурів фіксували в 10% розчині нейтрального формаліну, зневоднювали у висхідній батареї спиртів. Для виявлення астроцитів використовували GFAP mouse monoclonal antibody (Santa Cruz Biotechnology, inc.). Для виявлення нейронів використовували NeuN mouse monoclonal antibody (Santa Cruz Biotechnology, inc.). В гістологічних зрізах вивчали відносну площу, займану GFAP + і NeuN + клітинами. Дані оброблені методом варіаційної статистики. Результати достовірні при р <0,05. Утримання тварин та експерименти проводилися за міжнародними принципами Європейської конвенції про захист тварин, що використовуються для експериментальних та інших наукових цілей (Страсбург, 18.03.86) та Закону України № 1759-VI (15.12.2009) «Про захист тварин від жорстокого поводження». Результати. Щільність розподілу GFAP + клітин в гіпокампі і зубчастої звивини щурів хвилеподібно змінюється протягом перших півтора місяців постнатального життя. У потомства щурів після стимуляції родової діяльності на першу добу життя визначається достовірне збільшення відносної площі займаної GFAP + астроцитами в порівнянні з контролем (49,3±2,6% і 36,8±5,9% відповідно). У гіпокампі і зубчастої звивини потомства щурів після стимуляції родової діяльності протягом перших 45-ти діб після народження визначається поступове зменшення відносної площі, займаної NeuN + нейронами на відміну від контрольних тварин, у яких цей показник практично не змінюється.

Изучение особенностей развития гиппокампальной формации в постнатальном периоде после стимуляции родовой деятельности является актуальным. Цель. Изучить особенности экспрессии GFAP и NeuN в гиппокампальной формации потомства крыс после интравагинального введения PgE2 самкам для стимуляции родовой деятельности. Материалы и методы. Беременным самкам экспериментальной группы на двадцать второй день беременности для стимуляции родовой деятельности интравагинально вводили PgE2 в виде геля. Большие полушария головного мозга крыс фиксировали в 10% растворе нейтрального формалина, обезвоживали в восходящей батарее спиртов. Для выявления астроцитов использовали GFAP mouse monoclonal antibody (Santa Cruz Biotechnology, inc.), для выявления нейронов использовали NeuN mouse monoclonal antibody (Santa Cruz Biotechnology, inc.). В гистологических срезах гиппокампа и зубчатой извилины крыс изучали относительную площадь, занимаемую GFAP+ и NeuN+ клетками. Данные обработаны методом вариационной статистики. Результаты достоверны при р <0,05. Содержание животных и эксперименты проводились согласно международным принципам Европейской конвенции о защите животных, используемых для экспериментальных и других научных целей (Страсбург, 18.03.86) и Закона Украины № 1759-VI (15.12.2009) «О защите животных от жестокого обращения». Результаты. Плотность распределения GFAP+ клеток в гиппокампе и зубчатой извилине крыс волнообразно изменяется на протяжении первых полутора месяцев постнатальной жизни. У потомства крыс после стимуляции родовой деятельности на первые сутки жизни определяется достоверное увеличение относительной площади занимаемой GFAP+ астроцитами по сравнению с контролем (49,3±2,6% и 36,8±5,9 % соответственно). В гиппокампе и зубчатой извилине потомства крыс после стимуляции родовой деятельности на протяжении первых 45-ти суток после рождения определяется постепенное уменьшение относительной площади, занимаемой NeuN+ нейронами в отличие от контрольных животных, у которых этот показатель практически не изменяется.
Імуногістохімічна характеристика ішемічних процесів в гіпокампі та зубчастій звивині головного мозку потомства щурів після стимуляції пологів
Иммуногистохимическая характеристика ишемических процессов в гиппокампе и зубчатой извилине головного мозга потомства крыс после стимуляции родов
Keywords: labor stimulation; hippocampus; dentate gyrus; Glial fibrillary acidic protein; NeuN; стимуляція пологів; гіпокамп; зубчаста звивина; GFAP; стимуляция родов; гиппокамп